Mental Health and Psychological Wellbeing of Employees to Manage Post COVID-19 Crisis: Insights from Hospitality Industry - Bhuiyan, Kamrul Hasan; Kowser, Ali Mohammad; Santus Kumar Deb (Tecno Scientifica Publishing, 2024)
COVID-19 pandemic has driven the world towards socio-economic emergency and psychological distress. This unprecedented but far-reaching consequence has devastated the service sector, particularly the hospitality industry. The purpose of this study was to explore the impact of managing mental health as well as psychological wellbeing of the employees in the hospitality industry to manage the crisis of post COVID-19 in terms of depression, anxiety and stress. This study used quantitative research methods and data were collected from a sample of 253 employees of hospitality industry using a purposing sampling technique. More emphasize were given to Dhaka, Chattagram and Sylhet divisions due to proximity of hospitality properties. The cross-sectional survey form was designed to measure the mental health and psychological wellbeing of employees in the hospitality industry whereas DASS-21 (Depression, Anxiety and Stress Scale) was used as screening instrument. The multinomial logistic regression was used to test the relationship among the variables. The results of the study show that 52% of the respondents are suffering from moderate to severe level of depression, 66% of the respondents are suffering from moderate to extremely severe level of anxiety but almost 90% of the respondents are not stressed or have mild stress symptoms. In addition, likelihood test results of DASS-21 shows that pandemic had a significant negative impact on initiative to work, panic, and agitated for the employees of hospitality industry, which still have a dominance. The findings of this study will assist the researchers, top management; and government to understand mental health and psychology of employees.